Tshangla verb inflections: a preliminary sketch - Andvik, Erik (2024)
The Tshangla language is spoken predominantly in eastern Bhutan, where it is also known as Sharchhop-kha, the language of the Sharchhop or Sharchhokpa, i.e. 'people living in the East.' The number of speakers in Bhutan is approximately 140,000 (George van Driem, personal communication). As the largest of the non-official languages of Bhutan, it serves as a lingua franca for several smaller language groups in the eastern half of the kingdom. Tshangla of Bhutan is equivalent to the Cangluo language of south¬eastern Tibet, described by Zhang Jichuan (1986), earlier presented by Sun et al. (1980) as the Motuo Menba. However, the language described by Zhang and Sun is spoken in a cluster of communities geographically separated from Bhutan by several hundred miles, namely the region formerly known as Padma-bkod, located near the point where the Tsangpo River (Siang), crosses the McMahon Line. A comparison of Bhutanese Tshangla vocabulary with the word list given in Sun et al. (1980) indicates that there are very few differences in the speech of the two communities. This was also confirmed by the author's own data taken from speakers of the Padma-bkod dialect.3 Speakers from Bhutan, as well as speakers from Padma-bkod who have had contact with each other, report that they easily understand the speech of the other group.